Tionghoa peranakan pre-war novels: Freeing from the past and the colonial, and embracing Indonesia - Sim, Chee Cheng (Universiti Kebangsaan Malaysia, 2010)
The loyalty of the Tionghoa Peranakan (local-born Chinese) in Indonesia has often been considered circumspect. It has been the hypothesis of much research on the reasons for the racial riots that often resulted in the victimisation of the Tionghoa Peranakan. This article offers a glimpse of their various loyalties through an analysis of novels that are still available and were written by the Tionghoa Peranakan between 1903 and 1910, the pre-war period of the Dutch East Indies. These novels reveal some of the reasons for the Tionghoa Peranakan’s decisions on their future and Indonesian identity. Factors both historical and pertaining to a migrant milieu played a part in changing their point of reference from China and the Netherlands to Indonesia. Clinging onto a past that was unrealiable and cruel was not a choice just as gravitating towards a retreating Dutch was not feasible. While it appears that the Tionghoa Peranakan eventually cast their loyalty for Indonesia for economic reasons, the novels show that their migrant background had resulted in disillusionment with both China and the Dutch imperialists